2001
DOI: 10.1002/qua.1110
|View full text |Cite
|
Sign up to set email alerts
|

Phenol O–H bond dissociation energy in water clusters

Abstract: ABSTRACT:We are reporting ab initio and density functional theory (DFT) calculations for the phenol O-H bond dissociation energy in the gas phase and in phenol-water clusters. We have tested a series of recently proposed functionals and verified that DFT systematically underestimates the O-H bond dissociation energy of phenol. However, O-H bond dissociation energies in water clusters are in reasonable agreement with experimental data for phenol in solution. We have evaluated electronic difference densities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The numerous calculations of O−H BDE in phenol up to 1997 have been summarized by Borges dos Santos and Martinho Simoes . More recently, 13 different computational strategies yielded BDE(C 6 H 5 O−H)s ranging from 81.7 to 100.3 kcal mol -1 . Previous work by some of us using density functional theory (DFT) based methods gave values in the range 87.0 ± 0.3 or 87.9 ± 0.9 kcal mol -1 , depending on the level of theory at which the geometries were optimized and whether a (RO)B3LYP/6-311+G(2d,2p) or (U)B3P86/6-311G(2d,2p) approach was employed to calculate single point energies .…”
Section: Resultsmentioning
confidence: 99%
“…The numerous calculations of O−H BDE in phenol up to 1997 have been summarized by Borges dos Santos and Martinho Simoes . More recently, 13 different computational strategies yielded BDE(C 6 H 5 O−H)s ranging from 81.7 to 100.3 kcal mol -1 . Previous work by some of us using density functional theory (DFT) based methods gave values in the range 87.0 ± 0.3 or 87.9 ± 0.9 kcal mol -1 , depending on the level of theory at which the geometries were optimized and whether a (RO)B3LYP/6-311+G(2d,2p) or (U)B3P86/6-311G(2d,2p) approach was employed to calculate single point energies .…”
Section: Resultsmentioning
confidence: 99%
“…Enthalpies were also computed using two composite procedures, namely, CBS-Q and CBS-QB3, as well as with a dual (D,T) scheme to complete basis set extrapolation of CCSD(T) energies relying on cc-pVDZ and cc-pVTZ calculations proposed by Truhlar . This was necessary since previous works have shown that DFT behaves erratically in the determination of bond dissociation enthalpies. , The CBS methods, particularly CBS-QB3, as well as the (D,T) extrapolation, have shown to be adequate tools for the study of BDEs . The B3LYP/cc-pVTZ calculations were also used to determine Mulliken atomic spin densities for the radical species under study.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have shown phenol–phenol or phenol-water clusters can form in the gas-phase and produce stable clusters through hydrogen bonding. Theoretical simulations predict the stability of phenol-water clusters to be comparable to that of water clusters, exhibiting similar hydrogen bonding energies. , While no studies have investigated nitrophenol gas-phase clustering, these compounds are known to form both intra- and intermolecular hydrogen bonds; with very strong intramolecular hydrogen bonding observed between the nitro and hydroxyl group (C–NO–HO-C). Such interactions could result in stabilized cluster formation and new particle formation, potentially accounting for the observations shown in Sato et al (2012) and in this study; although this remains to be explained.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have shown phenol-phenol or phenol-water clusters can form in the gas-phase and produce stable clusters through hydrogen bonding [71][72][73][74] . Theoretical simulations predict the stability of phenol-water clusters to be comparable to that of water clusters, exhibiting similar hydrogen bonding energies 72,74 .…”
Section: Toluene and 4-methylmentioning
confidence: 99%